2011
DOI: 10.2215/cjn.04140510
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, Oxidative Stress, and Insulin Resistance in Polycystic Kidney Disease

Abstract: SummaryBackground and objectives Most deaths in autosomal dominant polycystic kidney disease (ADPKD) are attributable to cardiovascular disease (CVD). We examined novel CVD biomarkers in different stages of AD-PKD.Design, setting, participants, & measurements We recruited 50 hypertensive subjects with ADPKD with estimated GFR (eGFR) of Ͼ60 ml/min per 1.73 m 2 ; 52 hypertensive subjects with ADPKD with eGFR of 25 to 60 ml/min per 1.73 m 2 ; 42 normotensive subjects with ADPKD and eGFR of Ͼ60 ml/min per 1.73 m 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(109 citation statements)
references
References 28 publications
8
95
2
4
Order By: Relevance
“…We and others have shown that adult patients with ADPKD have elevated levels of cardiovascular disease risk and oxidative stress markers compared with healthy individuals (11)(12)(13)(14)(15) (Figure 1). These as well as inflammatory bioactive lipid mediators were elevated early in the disease and were associated with the increase in total kidney volume (TKV) and decline in renal function (14,16,17) (Figure 1).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…We and others have shown that adult patients with ADPKD have elevated levels of cardiovascular disease risk and oxidative stress markers compared with healthy individuals (11)(12)(13)(14)(15) (Figure 1). These as well as inflammatory bioactive lipid mediators were elevated early in the disease and were associated with the increase in total kidney volume (TKV) and decline in renal function (14,16,17) (Figure 1).…”
Section: Introductionmentioning
confidence: 89%
“…On the basis of this knowledge, we aimed to investigate whether the markers of endothelial dysfunction, inflammation, and oxidative stress identified in previous studies (11,(13)(14)(15)(16) (Figure 1) change in response to pravastatin therapy. This would qualify their use for monitoring of ADPKD disease progression and therapy efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…90 In comparison, oxidative stress was apparent even in patients with ADPKD with normotension versus healthy subjects and likely precedes the appearance of hypertension, which may account for the increased levels of angiogenic growth factors described in young patients with ADPKD. Several other serum and laboratory factors have been associated with various aspects of ADPKD severity, including serum uric acid, HDL, fibroblast growth factor-23, collagenderived peptides, NGAL, IL-8, and TNFa.…”
Section: Serum Copeptin Levelsmentioning
confidence: 99%
“…A wide range of factors that end up with structural myocardial disease are responsible for this adverse outcome. A variety of subclinical organ damage markers such as LVH, increased carotid intimamedia thickness, endothelial dysfunction, microalbuminuria, decreased coronary flow velocity reserve and low-grade systemic inflammation, and chronic oxidative stress have been reported in several studies of patients with ADPKD with wellpreserved renal function [26,27]. Functional data supporting a role of FGF-23 in vascular biology is derived from Klotho null mice, which carry no functional FGF-23 activity due to lack of coreceptors [28].…”
Section: Discussionmentioning
confidence: 99%